Regulation of Neurogenesis by FGF Signaling and Neurogenin in the Invertebrate Chordate Ciona - Kim, Kwantae; Gibboney, Susanne; Razy-Krajka, Florian; Lowe, Elijah K.; Wang, Wei; Stolfi, Alberto (Frontiers in Cell and Developmental Biology, 2020)
Neurogenesis is a complex sequence of cellular processes and behaviors driven by the coordinated expression of conserved effectors. The bipolar tail neurons (BTNs) of Ciona develop according to a highly dynamic, yet highly stereotyped developmental program and thus could serve as an accessible model system for neurogenesis, including underlying cell behaviors like neuronal delamination, migration, and polarized axon outgrowth. Here we investigate both the upstream events that shape BTN neurogenesis through spatiotemporal regulation of the conserved proneural factor Neurog, spatiotemporal, and the gene expression profile of differentiating BTNs downstream of Neurog activity. We show that, although early FGF signaling is required for Neurog expression and BTN specification, Fgf8/17/18 is expressed in tail tip cells at later stages and suppresses sustained Neurog expression in the anterior BTN (aBTN) lineage, such that only one cell (the one furthest from the source of Fgf8/17/18) maintains Neurog expression and becomes a neuron. Curiously, Fgf8/17/18 might not affect neurogenesis of the posterior BTNs (pBTNs), which are in direct contact with the Fgf8/17/18-expressing cells. Finally, to profile gene expression associated with BTN neurogenesis we performed RNAseq of isolated BTN lineage cells in which BTN neurogenesis was enhanced or suppressed by perturbing Neurog function. This allowed us to identify several candidate genes that might play conserved roles in neurogenesis and neuronal migration in other animals, including mammals.